Analisis Perilaku Pasar Komoditas Salak Pondoh (Salacca edulis reinwardt) Yang Dijual Di Pasar Tradisional - Himmatul Miftah; Elis Marfuah; Syaima Lailatul Mubarokah; Arti Yoesdiarti; Ikhsan Qodri Pramartaa (Jurnal Sosial Humaniora, 2023)
Salak pondoh has profitable agribusiness opportunities. The high level of population and tourists in Bogor City gave rise to many modern markets and traditional markets that provide fruits including pondoh salak. However, the characteristics of salak fruit that are easily damaged often in the process of distributing goods from producers to consumers there is an activity that triggers uncertainty. The quantity of actors involved in the marketing process can affect the marketing behavior of each marketing actor, so the research objective is to analyze market behavior by studying the process of price formation, the marketing chain, and the marketing function. The location selection was carried out purposively, namely Bogor Market and Jambu Dua Market which are markets that are mostly visited by the people of Bogor. The total number of respondents was 32 people consisting of 6 retailers, 5 collectors, and 21 farmers. The behavior of the pondoh salak market was analyzed using qualitative methods, namely the analysis of pricing practices, selling and buying practices of products from each marketer. Pricing at the farm level is determined by the next marketing agency, namely collecting traders, while at the trader level, pricing is carried out independently based on price information from the market. There is one marketing channel that is formed, namely farmers who sell to village collectors, village collectors sell to wholesalers, namely the Kramat Jati Market, wholesalers sell to Bogor City retailers and then sell to final consumers.